1987
DOI: 10.1254/jjp.44.335
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective action of histamine against 0.6N HCl-induced gastric mucosal injury in rats; Comparative study with adaptive cytoprotection induced by exogenous acid.

Abstract: Abstract-We examined the effects of histamine 2HCI (a stimulator of endogenous acid production) and exogenous acid on transmucosal potential difference (PD) and pH of anesthetized rat stomachs, in order to investigate the mechanism underly ing the protective action of histamine against 0.6 N HCI-induced gastric mucosal injury in conscious rats. Subcutaneously administered histamine (3-20 mg/kg) dose-dependently produced a decrease in the PD and pH, and it reduced the severity of gastric mucosal injury caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1989
1989
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 16 publications
0
6
1
Order By: Relevance
“…isoprenaline and forskolin) makes it difficult to correlate the effect of indomethacin to changes in cyclic AMP levels inside the parietal cells. A possible release of PGs by histamine, recently suggested by some authors [2,7] was not confirmed in our study, since no differences were found in PGs levels in the mucosal fluid before and after histamine stimulation. The use of immature animals may perhaps explain the low levels of PGs produced; the experiments carried out with arachidonic acid tend to exclude the possibility that the low production of PGs was due to an insufficient amount of substrate for the action of cyclooxygenase.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…isoprenaline and forskolin) makes it difficult to correlate the effect of indomethacin to changes in cyclic AMP levels inside the parietal cells. A possible release of PGs by histamine, recently suggested by some authors [2,7] was not confirmed in our study, since no differences were found in PGs levels in the mucosal fluid before and after histamine stimulation. The use of immature animals may perhaps explain the low levels of PGs produced; the experiments carried out with arachidonic acid tend to exclude the possibility that the low production of PGs was due to an insufficient amount of substrate for the action of cyclooxygenase.…”
Section: Discussioncontrasting
confidence: 85%
“…Recently a release of PGs by histamine has been observed in rats and the cytoprotective action of histamine in this species was ascribed to this effect [7]. The aim of the present study was to investigate the role of endogenous PGs in the secretory effect of histamine, by using different cyclooxygenase inhibitors and by measuring PGs production in the mucosal solution.…”
Section: Introductionmentioning
confidence: 95%
“…Six hours after the administration of the test compounds, the animals were euthanized. Excised stomachs were inflated with and fixed by immersion in 2% formalin [24], Then they were opened along the greater curvature. After rinsing with 2% formalin, the mucosa was examined for the presence of erosion under a binocular micro scope.…”
Section: Irritative Action On Tlw Rat Stomachmentioning
confidence: 99%
“…The response caused by 100 mM HCl is mediated only by PGs, whereas that caused by 200 mM HCl is mediated by both capsaicin-sensitive afferent neurons and NO in addition to endogenous PGs. We previously examined the effect of HCl at various concentrations (0.1ϳ0.35 M) on transmucosal PD of rat stomachs and found that the PD was not decreased by HCl even at 0.25 M (27). Thus, it is likely that 200 mM HCl, unlike 0.5 M NaCl, does not damage surface epithelial cells.…”
Section: Discussionmentioning
confidence: 99%